Desulphurisation of dibenzothiophene and 4,6 – dimethyl dibenzo¬thio-phene via enhanced hydrogenation reaction route using RePd–TiO2/SiO2 aerogel catalysts: Kinetic parameters estimation and modelling: Original scientific paper - Prokić-Vidojević, Dragana; Glišić, Sandra B.; Pešić, Radojica; Orlović, Aleksandar M. (HEMIJSKA INDUSTRIJA (Chemical Industry), 2022)
Re/Pd-TiO2/SiO2 aerogel catalysts were synthesized by using a sol-gel method and supercritical drying in excess solvent and investigated in the reaction of hydrodesulphurisation (HDS) of dibenzothiophene (DBT) and 4,6-dimethyl dibenzothiophene (4,6-DMDBT). Both Re/Pd catalysts, obtained with and without the use of mesitylene in the synthesis step, have shown increased conversions of up to 70 % in the desulphurization of 4,6-DMDBT, when compared to conventional Co/Mo hydroprocessing catalysts. This observation is of importance for conversion of highly refractory 4,6-DMDBT and hydroprocessing to produce ultra-low sulphur diesel fuels, ULSD. In order to quantify the extent of desulphurisation, which proceeds via a hydrogenation route, conversions of DBT and 4,6-DMDBT along with evolution of reaction products characteristic for the direct desulphurisation route and the hydrogenation route were monitored by using a gas chromatography–mass spectrometry (GC-MS) analytical technique. The reaction was performed at 630 K and 6 MPa in a batch catalytic reactor. The experimental results were used in the Hougen-Watson kinetic model describing DBT and 4,6-DMDBT desulphurisation on σ and τ active sites. Kinetic parameters of this complex catalytic kinetics were determined by using a Genetic Algorithm method and minimum deviation function. Values of calculated kinetic parameters and values of the ratio of 3-methylcyclohexyltoluene (MCHT and dimethyl biphenyl (DMBPH) expressed as the MCHT/(MCHT+DMBPH) ratio ranging between 0.66 and 0.94, have confirmed that the hydrogenation route is the dominant route for desulphurisation of 4,6-DMDBT.